Synthesis and Characterization of New4, 5-dihydrooxazole and 1H-imidazole-5(4H)-one Derivative and Study its Effects on some Antibacterial - Fadhel Omran Essa (Journal of Global Pharma Technology, 2016)
New1H-imidazole-5(4H)-one derivatives have been prepared to start from the reaction of 2-phenyl-4H-1, 3-benzoxazine-4-one with tyrosine. The reaction of compound 1 with thionyl chloride produced 3-(4-hydroxyphenyl)-2-(4-oxo-2-phenylquinazolin-3(4H)-yl)propanoyl chloride2. Condensation of compound 2 with glycine afforded 2-(3-(4-hydroxyphenyl)-2-(4-oxo-2-phenylquinazolin-3(4H)-yl)propanamido)acetic acid3.The reaction of compound 3with acetic acid, acetic anhydride, and benzaldehyde derivatives yielded 3-(1-(4-benzylidene-4,5-dihydrooxazol-2-yl)-2-(4-hydroxyphenyl)ethyl)-2-phenyl-quinazolin-4(3H)-one derivatives 4a-e.Treatment of compound 4a-d with hydrazine hydrategave3-(1-(1-amino-4-benzylidene-4,5-dihydro-1H-imidazol-2-yl)-2-(4-hydroxyphenyl)-ethyl)-2-phenylquinazolin-4 (3H)- one derivatives 5a-d. The reaction of compound 5a-d with benzaldehyde derivatives resulted in the formation of 3-(1-(-4-benzylidene-1-(benzylidene amino)-4, 5-dihydro-1H-imidazol-2-yl)-2-(4 hydroxyphenyl) ethyl)-2-phenyl-quinazolin-4(3H)-one6a-6b.The structure of novel synthesized compounds were assured from IR, 1HNMR, and13CNMR spectra.Keywords: Phenylquinazolines, Imidazole, Benzylideneamino, Dihydrooxazole.